Oral health knowledge, attitude, and practices among patients visiting a tertiary care center - KC, Monica; Gurung, Jyoti; Thapa, Sujan; Maharjan, Anjana (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Oral health is a critical component of overall well-being. Its neglect can contribute not only to dental diseases but also to systemic complications, increasing the burden on individuals and healthcare systems. Assessing patients’ knowledge, attitudes, and practices is therefore essential to identify existing gaps and inform the development of evidence-based preventive strategies and public health interventions aimed at achieving sustainable improvements in oral health outcomes. Method: A descriptive cross-sectional study was carried out among patients attending the dental department of Patan Hospital from 23 June 2025 to 25 July 2025. Data were collected using a structured, self-administered questionnaire assessing oral health knowledge, attitudes, and practices. Responses were categorized and scored, with levels classified according to Bloom’s cut-off criteria. Descriptive statistics, chi-square tests, and Pearson correlation analyses were performed using SPSS version 23. Result: Of the 324 participants, 21.9% demonstrated high knowledge, 48.7% had moderate knowledge, and 29.4% had low knowledge of oral health. Regarding attitude, the majority expressed positive perceptions. For practice, only 29.9% reported good oral health behaviors, 44.1% had fair practices, and 25.9% exhibited poor practices. No significant association was observed between gender and KAP levels. However, knowledge and attitude scores showed a significant positive correlation with oral health practice (p < 0.001). Conclusion: Although participants demonstrated moderate knowledge and, positive attitudes toward oral health, gaps in daily practices persist. The observed associations between knowledge, attitude, and practice highlight the importance of targeted educational and behavioral interventions to improve oral health outcomes.